Innovation approaches—Collective learning from the Fodder Adoption Project - Puskur, Ranjitha (International Livestock Research Institute, 2010)
After a session of the the November 2010 Fodder Adoption Project (FAP) workshop in Laos, we recorded 'notes' of three world cafe hosts who collated cross-project lessons (from Ethiopia, Syria, and Vietnam) on three issues: Innovation approaches, feed assessment, and scaling out. Here Ranjitha Puskur of ILRI reports on the lessons on innovation approaches that have been tried in the project. The collective learning by the group revealed that the countries practiced diverse approaches and processes; however these approaches seem to work well when there is a good balance between technologies and the process, there are good market opportunities, and the approach is 'hybridized' with the value chains approach. She points out that these approaches are quite complex and facilitation intensive, who brokers this facilitation is a key factor that influences the outcomes. For stakeholder platforms of the kind supported in the project to be effective, it is clear that the actors who need to be involved need to clearly see their role, the incentives, and benefits they will get and so develop commitment to the process. Two missing aspects are: 1) how to reach out to policymakers at various levels that would enable scaling up and out of the project outputs, and 2) how to target communities and households so the benefits of these processes are captured locally, and not by the elite. She raised one other significant issue: monitoring and evaluation. We talk of 'innovation capacity building' as something we do in such projects, but what do we mean by this, and how do we capture the unintended benefits of projects that employ such innovation approaches? Do we really know enough about such approaches overall? There seems to be a big agenda here for further research and learning.